Endovascular Treatment of Renal Artery Stenosis Caused by Fibromuscular Dysplasia. A Clinical Case Report - D. S. Chigidinova; N. E. Gavrilova; B. A. Rudenko; A. S. Shanoyan; V. P. Mazaev; F. B. Shukurov (Креативная хирургия и онкология, 2019)
Introduction. Fibromuscular dysplasia (FMD) is an idiopathic, non-atherosclerotic, non-inflammatory disease of arteries. Careful research into this disorder showed that FMD has been found in every arterial bed in the body; the most common arteries affected are renal arteries and extracranial sections of carotid and vertebral arteries. The clinical presentation is determined by the localization of the vasculature affected and the stenosis severity. Today FMD is a very rare disease with the incidence of 4 per 1000 people. The diagnosis today is difficult and may take a long time. According to the latest European Society of Cardiology guidelines renal artery balloon angioplasty is indicated for patients with FMD; if a good angiographic result is achieved (no dissection, TIMI 3 flow) no renal artery stenting required. The treatment success depends on the early diagnosis.Materials and Methods. This paper presents a clinical case of renal artery stenosis caused by fibromuscular dysplasia that was treated successfully with balloon angioplasty without stenting.Results and discussion. Protracted process of diagnosing this disease may result in deteriorating quality of life and poor outcomes such as difficult-to-control hypertension and its sequelae, TIA, stroke, aneurism dissection or rupture. It is worth pointing out that FMD diagnosis may be incidental when imaging is performed for other reasons, or when there is a systolic murmur at arteries in an asymptomatic patient who does not have classic atherosclerosis risk factors. According to the latest guidelines endovascular treatment is indicated for patients with FMD to manage the hypertension; this has proven very effective in improving quality of life.